EFISIENSI BIAYA PRODUKSI GAZEBO DENGAN APLIKASI MESIN PEMOTONG BAMBU DAN GLUGU - Hasan, Khojanah; Bahri, Syamsul (DINAMIKA DOTCOM, 2018)
Bamboo products such as Gazebo are bamboo handicrafts that require only small capital but can generate business opportunities with multiple profits and have tremendous prospects. Gazebo is one of bamboo handicraft which, if it is processed by creative hands, hence bamboo handicraft can be valued to millions of rupiah. As in the area of Pendem Village, Junrejo Sub-District Batu Tourism City was chosen to be an object because in that area there is a very active and enthusiastic Business Group in this entrepreneurship program, so it can be utilized by local people as a means to get a job and increase income welfare. The problem with this effort is the process of making bamboo and glugu gazebo this is all done manually one by one especially bamboo cutting process and making hole in bamboo and glugu, so it is not efficient and effective. In addition there are limitations about insight enterpreneur, management, marketing and making simple bookkeeping (accounting). The results of IbM activities that have been carried out by the Implementing Team, including the provision of bamboo and glugu cutting machine, drilling machine, operate and test the machine, training and mentoring both about entrepreneurship, management, marketing and simple accounting comprehension in order to optimize products more qualified, innovative , kratif can develop so as to compete with other similar industries.Â Keywords: Business group, Bamboo & glugu cutting machine, Gazebo, Efesien and effective